Thai Tourists Perceived Value of an Authenticity Management of Chiang Mai International Airport, Thailand: A Proposed Model of an Authenticity Management of Chiang Mai International Airport, Thailand - Anantakoon, Prapop; Choibamroong, Therdchai (Rajapark Journal, 2024)
This research aimed to 1) measure Thai tourists’ levels of the perceived value of authenticity management at Chiang Mai International Airport, Thailand, and 2) construct a model of authenticity management at Chiang Mai International Airport, Thailand. The sample was 400 Thai tourists at Chiang Mai International Airport, Thailand. They were selected by purposive sampling. The instrument for collecting data was a self-administered questionnaire—analysis of data by Descriptive Statistics and Inferential Statistics. The research results were found as follows; 1) Thai tourists with demographic differences had different levels of perceived value of airport attributes displaying Thai Lanna art and culture reference at Chiang Mai International Airport and 2) A model of an authenticity management of Chiang Mai International Airport, Thailand, comprised of 5 levels of perceived value: (1) Functional value; (2) Social value; (3) Emotional value; (4) Epistemic value and (5) Conditional value.